Single‐Molecule Spatial Arrangement: Strep‐Tag II and Monovalent Strep‐Tactin as Novel Handles in Single‐Molecule Cut‐and‐Paste (Small Methods 8/2017). Issue 8 (10th August 2017) - Erlich, Katherine R.; Baumann, Fabian; Pippig, Diana A.; Gaub, Hermann E.
Abstract : The cover image is a conceptual representation of the process of "single‐molecule cut‐and‐paste", a technique that enables directed assembly of nanoscale structures, which is presented by Hermann E. Gaub and co‐workers in article number1700169 . The storage area "A" of the surface contains several depot areas of biomolecules of interest. These biomolecules (represented by the colored fundamental shapes) are picked up one‐by‐one by the cantilever via a specific handling system (represented here by the hooks and eyelet). The molecules can then be arranged on the target area "B" in any geometry with nanometer‐precision. Cover image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).